Correlation of Maturity Parameters Derived from Methylphenanthrenes and Methyldibenzothiophenes in the Carboniferous Source Rocks from Qaidam Basin, NW China. (21st December 2019) - He, Chuan; Huang, Haiping; Wang, Qianru; Li, Zongxing
Abstract : Twenty-one core samples from the Carboniferous Keluke Formation in the Qaidam basin, NW China, have been geochemically characterized to investigate thermal maturation influence on the evolution behaviors of aromatic hydrocarbons and the validity of commonly used maturity parameters. The Keluke Formation was deposited in marine to continental transitional facies and dominated by type III kerogen. Rock-Eval T max and vitrinite reflectance (% R o ) measurement suggested that the studied samples are highly matured at peak oil to gas condensate generation stages. Most biomarkers lost their sensitivity to indicate maturity level due to either approaching the equilibrium point or too low concentrations, while isomer distributions in alkylnaphthalenes, alkylphenanthrenes, and alkyldibenzothiophenes still show systematic variations with increasing maturity. The present study focused on the maturity parameters derived from methylphenanthrenes (MP) and methyldibenzothiophenes (MDBT). The most widely used methylphenanthrene index 1 (MPI ‐ 1 = 1.5 × 2 ‐ MP + 3 ‐ MP / P + 9 ‐ MP + 1 ‐ MP ) shows no correlation with known maturity indicators, but the methylphenanthrene ratio (MPR = 2 ‐ MP / 1 ‐ MP ) and methyldibenzothiophenes ratio (MDR = 4 ‐ MDBT / 1 ‐ MDBT ) increase steadily with increasing maturity levels and are proved to be valid maturity parameters. However, empirical vitrinite reflectance estimations derived from MPR and MDR have dramatically overestimated the maturity levels. Our quantitative data illustrated that concentrations of thermally stable isomers (3-MP, 2-MP, and 4-MDBT) increase continuously with increasing maturity while thermally unstable isomers (9-MP, 1-MP, and 1-MDBT) are almost invariable in the studied maturity range. The invalidity of MPI-1 is caused by the involvement of phenanthrene in the maturity parameter formula possibly due to a variable degree of alkylation. Dealkylation of methylphenanthrenes to form parent phenanthrene occurs much earlier than R o of 1.35% reported in the literature. The increment of MPR and MDR values with maturity levels is mainly caused by different generation rates with a higher generation rate of thermally stable isomer than thermally unstable counterpart rather than isomerization between them. Caution should be taken when empirical formula published in literature based on commonly used maturity parameters is directly applied for maturity estimation as no universal applicable correlation is likely available.